A 3-month jump-landing training program: a feasibility study using the RE-AIM framework - Aerts, I.; Cumps, E.; Verhagen, E.; Mathieu, N.; Van Schuerbeeck, S.; Meeusen, R. (Journal of Athletic Training, 2013)
Context: Evaluating the translatability and feasibility of an intervention program has become as important as determining the effectiveness of the intervention. Objective: To evaluate the applicability of a 3-month jump-landing training program in basketball players, using the RE-AIM (reach, effectiveness, adoption, implementation, and maintenance) framework. Design: Randomized controlled trial. Setting: National and regional basketball teams. Patients or Other Participants: Twenty-four teams of the second highest national division and regional basketball divisions in Flanders, Belgium, were randomly assigned (1:1) to a control group and intervention group. A total of 243 athletes (control group = 129, intervention group = 114), ages 15 to 41 years, volunteered. Intervention(s): All exercises in the intervention program followed a progressive development, emphasizing lower extremity alignment during jump-landing activities. Main Outcome Measure(s): The results of the process evaluation of the intervention program were based on the 5 dimensions of the RE-AIM framework. The injury incidence density, hazard ratios, and 95% confidence intervals were determined. Results: The participation rate of the total sample was 100% (reach). The hazard ratio was different between the intervention group and the control group (0.40 [95% confidence interval = 0.16, 0.99]; effectiveness). Of the 12 teams in the intervention group, 8 teams (66.7%) agreed to participate in the study (adoption). Eight of the participating coaches (66.7%) felt positively about the intervention program and stated that they had implemented the training sessions of the program as intended (implementation). All coaches except 1 (87.5%) intended to continue the intervention program the next season (maintenance). Conclusions: Compliance of the coaches in this coach-supervised jump-landing training program was high. In addition, the program was effective in preventing lower extremity injuries.